Hyper-Reactivity to Salience Limits Social Interaction Among Infants Born Pre-term and Infant Siblings of Children With ASD - Zivan, Michal; Morag, Iris; Yarmolovsky, Jessica; Geva, Ronny (Frontiers in Psychiatry, 2021)
The ability to engage attention with selected stimuli is essential for infants to explore the world and process information relating to their surroundings. There are two main populations with a higher risk to develop attentional and social deficits whose deficits may arise from difficulties in regulating attention to salient cues: 1) siblings of children diagnosed with Autism; and 2) infants who were born preterm. This study investigated infants' (N=97) attention-engagement and pupil-dilation (PD) at 9m., using a gaze-contingent paradigm and a structured social interaction. Specifically, we explored attention to stimuli with simple salient features (e.g. clear defined shapes, colors and motions) vs. more complex non-social cues (amorphous shapes, colors and motions) and social interaction in typically developing infants (TD, N=25) and among two groups of infants at-risk to develop social difficulties (preterms, N=56; siblings of children with Autism, N=16). Findings show that the two risk groups preferred stimuli with simple features (F=11.306, p<0.001), accompanied by increased PD (F=6.6, p<0.001). Specifically, preterm infants showed increased PD toward simple vs. complex stimuli (p<0.001), while siblings showed a pervasive hyper-arousal to both simple and complex stimuli. Infants in the TD group preferred complex stimuli with no change in PD. Finally, the preference for the simple stimulus mediated the relationship between increased risk for social difficulties and decreased engagement duration in face-to-face interaction with the experimenter . Results suggest that activation of the attention-salience network shapes social abilities at infancy. Further, hyper-reactivity to salient stimuli limits social interaction among infants born preterm and siblings of children with ASD.